Decay Timescales of Chromospheric Condensations in Solar Flare Footpoints - Elizabeth C. Butler; Adam F. Kowalski (The Astrophysical Journal, 2024)
Chromospheric condensations (CCs) are a prominent feature of flare footpoint heating in the solar flare standard model, yet their timescales and velocities are not well understood. Fisher derived several important analytical relationships, which have rarely been examined with modern spectral observations. The Interface Region Imaging Spectrograph (IRIS) provides a wealth of flare data with a high enough cadence to sufficiently capture CC evolution. We analyzed Doppler shifts in Mg ii 2791 and Fe ii 2814 from a sample of flare footpoint pixels observed by IRIS to compare with Fisher's analytics and recent flare models. We found a detection lifetime of 1 minute occurs in 50% of the sample, with Mg ii showing several pixels with longer values and Fe ii almost categorically shorter, and both growing with the maximum velocity, v _max . The shifts’ half-life is commonly <40 s and is inversely related to v _max , indicating that the first half of the CC evolution has more efficient kinetic energy loss. The lifetime’s wide range and growth with v _max indicate that the footpoint atmospherics and heating scenarios can vary more widely than first postulated in Fisher. Around 90% of the sample had observable acceleration periods, lasting an average of 38 and 32 s for Mg ii and Fe ii , respectively. These acceleration periods, as well as serving as flare model diagnostics themselves, could potentially be used to calculate other model diagnostics such as the initially accelerated mass.